Maud JL Graff. Effectiveness and efficiency of community based occupational therapy for older people with dementia and their caregivers - van 't Leven, Netta; Graff, Maud J. L.; Vernooij-Dassen, M.; Olde Rikkert, Marcel G. M. (Tijdschrift voor Gerontologie en Geriatrie, 2008)
bespreking proefschrift Maud JL Graff. Effectiveness and efficiency of community based occupational therapy for older people with dementia and their caregivers. Academisch proefschrift Radboud Universiteit Nijmegen, faculteit Medische Wetenschappen, 2008.